Alih Kode dan Campur Kode dalam Diskusi Mahasiswa Teknik Informatika Universitas PGRI Madiun - Estuning Dewi Hapsari (Universitas Nahdlatul Wathan Mataram, 2020)
This analysis has a purpose to know the code and mix code in class discussions. In addition, it is also to know the purpose of the Code and mix code. The data is obtained through the observation of formal discussion activities in Indonesian language courses. The collected Data is transcribed in a text form. This type of research is a qualitative descriptive, which describes in a tangible and factual form about the fact that the field is researched. The study was conducted for 4 months, starting in February and until May. During the study, researchers conducted three research studies covering the preparation stage, implementation stage, and completion stage. Data collection techniques, such as: observation, documentation, and interview. Based on data analysis, it is possible to conclude that code and code mix occurs in three languages. The language is Indonesian language Indonesiam, and English. Code and code encoding can occur from Bahasa Indonesia into Javanese language and from Bahasa Indonesia into English. Code and code-mixing objectives can be identified by context. These objectives include; (1) Facilitate the conveying of the material, (2) quoting the figure's opinion, (3) diverting the atmosphere in order not to strain, and (4) offset the interlocutor.